Belantamab Mafodotin for the Treatment of Multiple Myeloma: An Overview of the Clinical Efficacy and Safety - Offidani M; Corvatta L; Morè S; Olivieri A (Dove Medical Press, 2021)
Massimo Offidani,1 Laura Corvatta,2 Sonia Morè,1 Attilio Olivieri1 1Clinica di Ematologia Azienda Ospedaliero-Universitaria, Ospedali Riuniti di Ancona, Ancona, Italy; 2U.O.C. Medicina, Ospedale Profili, Fabriano, ItalyCorrespondence: Massimo OffidaniClinica di Ematologia Azienda Ospedaliero-Universitaria, Ospedali Riuniti di Ancona, Via Conca, 71, Ancona, 60020, ItalyTel +390715964735Email massimo.offidani@ospedaliriuniti.marche.itAbstract: Despite the introduction of immunomodulatory drugs (IMiDs), proteasome inhibitors (PIs), and, more recently, monoclonal antibodies (mAbs), in the chemotherapy regimens for newly diagnosed (NDMM) and relapsed/refractory MM (RRMM), the occurrence of drug resistance remains a challenge in MM patients. This is mainly in the advanced stage of the disease when treatments are limited, and the prognosis is abysmal. Nevertheless, novel molecules and therapeutic approaches are rapidly moving through the several phases of drug development and could address the need for new treatment options. The recent innovative B-cell maturation antigen (BCMA) targeted immunotherapies, such as belantamab mafodotin, the first-in-class monoclonal antibody-drug conjugate (ADC), induce an effective and durable response in triple-class refractory disease and to be approved in MM. In contrast with the other BCMA-targeted therapies as CAR T cells with a complex manufacturing process, and bispecific antibodies, both requiring inpatient hospitalization to monitor the occurrence of severe adverse events, belantamab mafodotin is an “off-the-shelf” drug that can be administered in an outpatient setting. Many belantamab mafodotin-based combinations are under evaluation in Phase I, II, and III clinical trials either late or in early RRMM patients. Ocular toxicity represents a peculiar side effect of belantamab mafodotin. This toxicity is generally manageable with adequate dose reductions or delays since most patients who developed keratopathy recovered on treatment and discontinued ADC are rare. Here, we described the most recent clinical data of belantamab mafodotin and discussed the possible leading role of this intriguing agent in the near future of MM treatment.Keywords: multiple myeloma, relapsed, refractory, belantamab mafodotin, antibody-drug conjugate